Serum CA 15-3 is increased in pulmonary fibrosis - Ricci, A.; Mariotta, S.; Bronzetti, et al., E. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2009)
Background and aim of the work: Carbohydrate antigen CA 15-3 is a glycoprotein whose expression, aberrant intracellular localization and changes in glycosylation have been associated with a wide range of cancers. Pulmonary fibrosis represents the final evolution of a chronic inflammation and is defined by the overgrowth of fibroblasts and exaggerated extracellular matrix deposition. The aim of the present study was to evaluate the possible diagnostic role of CA 15-3 in fibrosis in different idiopathic interstitial pneumonias. Methods: CA 15-3 was measured in serum samples from healthy subjects (n=25) and patients affected with idiopathic pulmonary fibrosis (IPF/UIP) (n=20), sarcoidosis (n=22) at different stages (I, II, and III) and systemic sclerosis (n=25). CA 15-3 protein expression was also evaluated by immunohistochemistry in 21 lung biopsies and in 6 primary lung fibroblasts cell lines. Results: The CA 15-3 serum levels were significantly higher in patients with IPF/UIP and with clinically advanced sarcoidosis (stage III). Serum CA 15-3 levels were slightly increased in patients with systemic sclerosis.No difference was observed between serum CA 15-3 levels in patients with sarcoidosis at stages I and II compared with control subjects. In IPF/UIP and in sarcoidosis at stage III elevated CA 15-3 serum levels significantly correlated with decreased total lung capacity, decreased diffusing capacity of carbon monoxide and high resolution computed tomography findings. Immunohistochemical analysis showed an intense specific CA 15-3 staining in fibroblasts within fibroblastic foci, surrounding sarcoid granulomas and in all cell cultures of lung fibroblasts from IPF/UIP lungs. Conclusions: Our results indicate that increased CA 15-3 levels are associated with pulmonary interstitial damage, fibroblast activity and progression to fibrosis of the lung. Therefore, CA-15-3 may be considered a sensitive marker useful in the identification of patients with advanced fibrosis and more severe prognosis.